2021
DOI: 10.14423/smj.0000000000001326
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Sexual Function Improve after Both Myomectomy and Hysterectomy for Symptomatic Fibroids

Abstract: Objectives: To determine the factors that influence the choice of myomectomy, uterine fibroid embolization (UFE), or hysterectomy in women with symptomatic uterine fibroids and to assess women's perception of body image and sexual functioning before and after treatment. Methods:In this prospective observational cohort pilot study, women scheduled to undergo hysterectomy, myomectomy, or UFE were surveyed before surgery and again at 3 to 6 months after their procedure to assess body image and sexual function usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, laparoscopic myomectomy is an alternative treatment for fibroids in women who want to preserve the uterus. In addition, the perception of hysterectomy has recently changed [ 31 ]. Nevertheless, women with lower incomes prefer hysterectomy because it is cheaper and safer without the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, laparoscopic myomectomy is an alternative treatment for fibroids in women who want to preserve the uterus. In addition, the perception of hysterectomy has recently changed [ 31 ]. Nevertheless, women with lower incomes prefer hysterectomy because it is cheaper and safer without the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the opinions among researchers are also conflicting (Birsen et al, 2018;Ferrandina et al, 2020;Frumovitz et al, 2020;Hartmann et al, 2004;Helström & Nilsson, 2005;Mann et al, 2020). Some studies have suggested that hysterectomy could reduce symptoms of depression and anxiety, increase general well-being (Aziz et al, 2005;Mattsson et al, 2020;Persson et al, 2010), and improve their interpersonal functioning in terms of a better perception of the body image and sexual functioning (Klock et al, 2021;Pauls, 2010). However, other researchers found evidence of a decrease in well-being and in the quality of life (Darwish et al, 2014;Khastgir et al, 2000;McPherson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%